Acute Myocardial Infarction across the Continuum of Care: Examining Care, Costs, Outcomes and Equity - Deborah, Cohen (Université d'Ottawa / University of Ottawa, 2014)
Among the manifestations of cardiovascular disease, acute myocardial infarction (AMI) holds a place of prominence in Canadian health policy. AMI is the number one cause of death for heart disease in Canada and costs the system over 500 million dollars in hospital stays annually. Because of the significant population-wide health and economic impact of AMI, disease management strategies that maximize health outcomes and minimize AMI’s overall burden to society are key areas of health policy research in Canada. For decades policy makers in healthcare have pointed to challenges with system fragmentation and the role of the continuum of care for diseases such as AMI, to optimize patient outcomes within limited healthcare budgets. Despite these concerns, there is a surprising lack of research focused on the care continuum for AMI. Instead much of the existing research continues to focus on AMI care, cost, outcomes and equity within a particular sector of care. Consequently, there remains a lack of baseline knowledge about patient care trajectories for AMI starting from preventive primary care, to treatment received in acute care, to corresponding patient outcomes. To address this gap in the knowledge base, this thesis dissertation takes a broad system view of AMI across the continuum of care, and examines the system with a patient-centric perspective. This research examines the patient care trajectory and puts forward baseline information on AMI care, cost, outcomes and equity that can be used in future research and policy initiatives to advance the continuum of care approach for AMI in Canada.
Keywords: Acute Myocardial Infarction; Care; Cost; Outcomes; Equity; Continuum of care